Close association between lifestyle and circulating FGF21 levels: A systematic review and meta-analysis - Qian, Zonghao; Zhang, Yucong; Yang, Ni; Nie, Hao; Yang, Zhen; Luo, Pengcheng; Wei, Xiuxian; Guan, Yuqi; Huang, Yi; Yan, Jinhua; Ruan, Lei; Zhang, Cuntai; et al. (Frontiers in Endocrinology, 2022)
Background: The impact of lifestyle factors on circulating fibroblast growth factor 21 (cFGF21) remains unclear. We conducted this systematic review and meta-analysis to evaluate the association between lifestyle factors and cFGF21 levels. Methods: We included studies that evaluated the effects of different lifestyles on cFGF21 concentration in adults, which included smoking, exercise, diets, alcohol consumption and weight loss. Random effects models or fixed effects models were used for meta-analysis to calculate the standardized mean difference (SMD) and 95% confidence interval according to the heterogeneity among studies. Study quality was assessed using the Newcastle–Ottawa Scale for cohort studies, the Joanna Briggs Institution Checklist for cross-sectional studies, and the PEDro scale for experimental studies. Results: A total of 50 studies with 1438 individuals were included. Overall, smoking, a hypercaloric carbohydrate-rich diet, a hypercaloric fat-rich diet, amino acid or protein restriction, excessive fructose intake and alcohol consumption significantly upregulated cFGF21 levels (p<0.05), whereas fish oil intake and calorie restriction with sufficient protein intake significantly decreased cFGF21 (p<0.05). Compared to the preexercise cFGF21 level, the cFGF21 level significantly increased within 3 hours postexercise (p<0.0001), while it significantly decreased in the blood sampled >6 h postexercise (p=0.01). Moreover, higher exercise intensity resulted in higher upregulation of cFGF21 at 1-hour post exercise (p=0.0006). Conclusion: FGF21 could serve as a potential biomarker for the assessment of different lifestyle interventions. When it is used for this purpose, a standard study protocol needs to be established, especially taking into consideration the intervention types and the sampling time post-intervention. Systematic Review Registration: https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42021254758 (ID: CRD42021254758)